Synthesis of rutile TiO2 nanostructures by single step hydrothermal route and its characterization. (2020) - Wategaonkar, S.B.; Pawar, R.P.; Parale, V.G.; Nade, D.P.; Sargar, B.M.; Mane, R.K.
Abstract: Today, an alternative source of renewable energy is dye - sensitized solar cell (DSSC) which works on a simple photosynthetic electrochemical principle. As TiO2 has great potential to absorb photon energy from solar sources, it is widely used for DSSC. This paper reports Nano sized TiO2 material with rutile phase is synthesized by a simple single step hydrothermal route on FTO substrate. Titanium (IV) isopropoxide as a precursor is used for the synthesis of TiO2 nanostructure. To study the effect of the quantity of TTIP precursor on the growth of TiO2, the film synthesized by a taking 0.9 ml TTIP. The crystalline structure, surface morphology, functional group, and elemental composition are characterized by X-Ray diffraction (XRD), Scanning Electron Microscopy (SEM), FT-IR Spectrometer & Energy Dispersive Spectroscopy (EDX) respectively. The rutile TiO2 has been a micro flower in shape at a hydrothermal temperature of 140° C for 3 hours. Hydrothermal treatment increased the tendency of crystal growth